Endoscopic ultrasound‐guided gallbladder drainage with a combined internal and external drainage tubes for acute cholecystitis. Issue 10 (28th April 2020) - Matsubara, Saburo; Isayama, Hiroyuki; Nakai, Yousuke; Kawakubo, Kazumichi; Yamamoto, Natsuyo; Saito, Kei; Saito, Tomotaka; Takahara, Naminatsu; Mizuno, Suguru; Kogure, Hirofumi; Ishizawa, Takeaki; Arita, Junichi; et al.
Abstract: Background and Aim: Lumen‐apposing metal stent is widely used for endoscopic ultrasound‐guided gallbladder drainage (EUS‐GBD) nowadays but not approved in many countries and might be unsuitable for elective laparoscopic cholecystectomy (LC) because of its large enterocholecysto fistula. A combination of double pigtail plastic stent (DPPS) and naso‐cystic tube (NCT) could overcome these problems. The aim of this study was to estimate the efficacy and safety of this method in patients with acute cholecystitis unfit for urgent cholecystectomy both as bridge to surgery and palliation. Methods: This was a prospective, single‐center feasibility study. EUS‐GBD was performed with a 7Fr DPPS followed by an NCT placement. NCT was removed after 1 week. LC was performed 2 or 3 months after EUS‐GBD in eligible patients. In patients who did not underwent cholecystectomy, DPPS was left in place. Results: Twenty‐three patients were enrolled. Both technical and clinical success rates were 96% (22/23). Early adverse events rate was 13% (3/23), including one bile peritonitis, one intraperitoneal abscess, and one melena. LC was attempted in 12 patients, and conversion to open cholecystectomy was required in three (25%). Neither recurrence of cholecystitis nor late adverse event occurred during 6 months of follow up in 10 patients who did not undergo cholecystectomy. Conclusion: EUS‐GBD with a combination of DPPS and NCT is considered an effective and safe technique both as bridge to surgery and palliation.